Effect of a microencapsulated phyto/phycogenic blend supplementation on growth performance, processing parameters, meat quality, and sensory profile in male broilers - Mullenix, Garrett J.; Greene, Elizabeth S.; Ramser, Alison; Maynard, Clay; Dridi, Sami (Frontiers in Veterinary Science, 2024)
Powered by consumer taste, value, and preferences, natural products including phytogenics and algae are increasingly and separately used in the food systems where they have been reported to improve growth performance in poultry and livestock. The present study aimed to determine the effects of a new feed additive, microencapsulated NUQO © NEX, which contains a combination of phytogenic and phycogenic, on broiler growth performance, blood chemistry, bone health, meat quality and sensory profile.Male Cobb500 chicks (n=1,197) were fed a 3-phase feeding programintervals; 01-14d starter, 15-28d grower, and 29-40d finisher. The dietary treatments included a corn-soy basal Control (CON), basal diet supplemented with NUQO© NEX at 100 g/ton from 01-28 d then 75 g/ton from d 28-39 40 (NEX75), and basal diet supplemented with NUQO© NEX at 100 g/ton from 01-39 40d (NEX100). The NEX100 supplemented birds had 62g more BWG increase and 2.1-point improvement in FCR compared with CON in the finisher and overall growth phase (P < 0.05), respectively. Day 40 processing body weights and carcass weights were heavier for the NEX100 supplemented birds (P < 0.05). The incidences of muscle myopathies were also higher in NEX treatments, which could be associated with the heavier weights, but the differences were not detected to be significant. The NEX75 breast fillets had more yellowness than other dietary treatments (P = 0.003) and the NEX 100 treatment reduced the levels of breast filet TBARS at 7 days-post harvest (P = 0.053). Finally, both NEX treatments reduced the incidence of severe bone (tibia and femur) lesions. In conclusion, the supplementation of the phytogenic NUQO © NEX improved finisher performance parameters, whole phase FCR, processing carcass weights, and breast fillet yellowness, at varying inclusion levels.